2020
DOI: 10.3389/fnins.2020.00738
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Mobile HRV Biofeedback as Adjunctive Therapy During Inpatient Psychiatric Rehabilitation Facilitates Recovery of Depressive Symptoms and Enhances Autonomic Functioning Short-Term: A 1-Year Pre–Post-intervention Follow-Up Pilot Study

Abstract: Objective: New treatment options for depression are warranted, due to high recurrence rates. Recent research indicates benefits of heart rate variability biofeedback (HRVBF) on symptom recovery and autonomic functioning in depressed individuals. Slowpaced breathing-induced amplification of vagus nerve activity is the main element of HRVBF. Thus, the latter represents a safe and non-invasive complementary depression treatment. However, its efficacy in patients undergoing inpatient psychiatric rehabilitation rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 103 publications
0
18
0
Order By: Relevance
“…Probably, this training was too short or too difficult to change the blood-flow in brain areas related to interoception [ 17 ]. Nevertheless, the absence of a performance increase argues against a strong optimization effect of the current breathing intervention [ 18 , 34 ] and future studies should probably apply trainings with longer durations [ 44 ] or should investigate coherent breathing as an acute strategy to modulate cardiac perception.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, this training was too short or too difficult to change the blood-flow in brain areas related to interoception [ 17 ]. Nevertheless, the absence of a performance increase argues against a strong optimization effect of the current breathing intervention [ 18 , 34 ] and future studies should probably apply trainings with longer durations [ 44 ] or should investigate coherent breathing as an acute strategy to modulate cardiac perception.…”
Section: Discussionmentioning
confidence: 99%
“…HR and respiration only oscillate at the same resonance frequency when the normal breathing frequency, usually between 0.15 and 0.4 Hz (9 and 24 breaths/minute), is rhythmically stimulated by paced breathing at an average frequency of 0.1 Hz. In general, breathing at 0.1 Hz also exercises the baroreflex to enhance context-specific regulation of blood pressure, and leads to the most efficient gas exchange and produces meditation- or mindfulness-related effects by focusing the attention on one’s breathing [ 6 , 9 , 10 , 13 ] (for overviews of the psychophysiological mechanisms and effects of slow breathing techniques see [ 10 , 14 , 15 ]) Several RFT studies have demonstrated that breathing at a rate of 0.1 Hz clinically improves symptoms of physical and mental disorders (for a summary, see [ 6 ]) including asthma [ 16 ], Posttraumatic Stress Disorder [ 17 , 18 ], and depression [ 19 , 20 , 21 ]. Most clinical studies exist for anxiety and cardiovascular disorders, where there is strong evidence of a small to medium effect of RFT [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, no changes in HRV could be detected between women having received CPI and those who did not. Previous integration of HRV biofeedback in MDD and anxiety patients mostly reported an increase in some functional parameters related to HRV [24]. However, the intervention applied here was considerably shorter compared to other studies on HRV biofeedback that usually implemented a training time of 6-10 weeks [25,26,63,64].…”
Section: Discussionmentioning
confidence: 88%
“…Reduced heat rate variability (HRV) is a recognized feature of MDD [22], indicating impaired cardiac adaptation to new stimuli and stress [23]. Interventions aimed at increasing HRV have just recently been added to antidepressant protocols, mostly as an augmentation to cognitive behavioral psychotherapy [24][25][26].…”
Section: Introductionmentioning
confidence: 99%